Optimization of inertial sensor-based motion capturing for magnetically distorted field applications - Schiefer, Christoph; Ellegast, Rolf P; Hermanns, Ingo; Kraus, Thomas; Ochsmann, Elke; Larue, Christian; Plamondon, André (Journal of biomechanical engineering, 2014)
Inertial measurement units (IMU) are gaining increasing importance for human motion tracking in a large variety of applications. IMUs consist of gyroscopes, accelerometers, and magnetometers which provide angular rate, acceleration, and magnetic field information, respectively. In scenarios with a permanently distorted magnetic field, orientation estimation algorithms revert to using only angular rate and acceleration information. The result is an increasing drift error of the heading information. This article describes a method to compensate the orientation drift of IMUs using angular rate and acceleration readings in a quaternion-based algorithm. Zero points (ZP) were introduced, which provide additional heading and gyroscope bias information and were combined with bidirectional orientation computation. The necessary frequency of ZPs to achieve an acceptable error level is derived in this article. In a laboratory environment the method and the effect of varying interval length between ZPs was evaluated. Eight subjects were equipped with seven IMUs at trunk, head and upper extremities. They performed a predefined course of box handling for 40 min at different motion speeds and ranges of motion. The orientation estimation was compared to an optical motion tracking system. The resulting mean root mean squared error (RMSE) of all measurements ranged from 1.7 deg to 7.6 deg (roll and pitch) and from 3.5 deg to 15.0 deg (heading) depending on the measured segment, at a mean interval-length of 1.1 min between two ZPs without magnetometer usage. The 95% limits of agreement (LOA) ranged in best case from -2.9 deg to 3.6 deg at the hip roll angle and in worst case from -19.3 deg to 18.9 deg at the forearm heading angle. This study demonstrates that combining ZPs and bidirectional computation can reduce orientation error of IMUs in environments with magnetic field distortion.